2005
DOI: 10.1097/00042737-200503000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oesophageal bolus transport in patients with mild oesophagitis

Abstract: In patients with mild GORD concurrent impedancometry and manometry is sufficiently sensitive for the detection of minor oesophageal dysmotility. Several pathological features have been characterized including delayed bolus transport, impaired propulsive volume clearance, pathological transport patterns and pathological reflux patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
1
27
1
2
Order By: Relevance
“…Domingues et al [29] have reported abnormal esophageal bolus clearance in patients with mild esophagitis. In their study, although the swallows have been further characterized into different patterns of impaired esophageal transport in their GERD patients, the vast majority of all swallows were manometrically normal in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Domingues et al [29] have reported abnormal esophageal bolus clearance in patients with mild esophagitis. In their study, although the swallows have been further characterized into different patterns of impaired esophageal transport in their GERD patients, the vast majority of all swallows were manometrically normal in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, impedance rises in phases of low conductivity when the air is present or pressure is applied to the electrodes by the muscular wall of the esophagus. In addition to the electrode array, the combination probe also has regular manometry channels that register pressure changes in the esophageal lumen [11][12][13]. Figure 2 shows a typical tracing of impedance in the healthy esophagus.…”
Section: Methods Of Combined Impedance Manometrymentioning
confidence: 99%
“…Domingues performed impedance manometry to establish physiologic pressure and impedance values in 25 healthy volunteers (14 males and 11 females; average age=34 years) [11]. In the region of the UES (CH1, CH2 in Fig.…”
Section: Impedance Manometry In Healthy Human Subjectsmentioning
confidence: 99%
“…27 However, patients with mild oesophagitis showed a slightly slower transit and an increased basal impedance gradient, suggesting persistence of mucosal bolus residues in the distal oesophagus. Postfundoplication dysphagia was evaluated in 80 consecutive patients by combined impedancemanometry.…”
Section: Clinical Studiesmentioning
confidence: 98%